Evaluation of antioxidative and antibacterial activities of fractionated hydrolysate from shrimp Litopenaeus vannamei head wastes against aquatic pathogenic bacteria - Rashidian, Ghasem; Abedian Kenari, Abdolmohammad; Nikkhah, Maryam (Aquaculture research, 2021)
The present study was aimed to evaluate in vitro antioxidant and antibacterial activities of fractions derived from white leg shrimp (Litopenaeus vannamei) head wastes hydrolysate. The shrimp waste hydrolysate (SWH) was generated using alcalase 2.4 L and sequentially fractionated using 3, 10, and 30 kDa molecular weight cut‐offs ultrafilters (Amicon®). The following permeates of P <3, 3< P <10, and 10<P< 30 kDa were collected and freeze‐dried hereafter referred to as F1, F2, and F3 respectively. Antioxidant activity of different concentrations (0.1, 0.5, 1, 2, and 3 mg/ml) of fractions were evaluated through 2,2‐diphenyl‐1‐picryl‐hydrazyl‐hydrate (DPPH) and 2,2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic acid (ABTS) radical scavenging activity and ferric reducing antioxidant power assay (FRAP). Standard disk diffusion test and microdilution methods were employed to determine inhibition zone (mm), minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) against Streptococcus iniae and Yersinia ruckeri. Results revealed that F1 exerts potent antioxidant activities with 84%, 78%, 46% of DPPH, ABTA, and FRAP scavenging power respectively (p < 0.05). However, no significant difference was found between F1 and F2 at 0.5 and 1 mg/ml concentrations. Antimicrobial results showed higher inhibition zones with F1 and less MIC and MBC concentrations of 0.1 and 0.5 mg/ml, respectively. Present findings revealed that fractions smaller than 10 kDa (F1 and F2) from shrimp head wastes hydrolysate can be considered as potent natural antioxidants at concentrations of 0.1–3 mg/ml as well as antimicrobial agents against S. iniae and Y. ruckeri (at 1, 2, and 3 mg/ml concentration).